Dora the Explorer. Undercover Dora - Herles, Kathleen, 1991-; Weiner, Marc.; Gifford, Chris; Walsh, Valerie; Weiner, Eric.; Nickelodeon Studios (Firm); Paramount Home Entertainment (Firm) (Hollywood, Calif. : Paramount Home Entertainment, 2008)
Dora and Boots become secret agents, assigned with stopping the crafty Swiper from stealing cupcakes and birthday presents.
Super spies, part 1 -- Super spies, part 2 -- Pinto, the Pony Express -- Rojo, the Red Fire Truck.
Created by Chris Gifford, Valerie Walsh and Eric Weiner.
Originally released in 2007.
"Nickelodeon."
Voices: Kathleen Herles, Harrison Chad, Sasha Toro, Marc Weiner.
Not rated.
DVD; full screen (1.33:1) presentation.
Keywords: Dora the Explorer (Fictitious character) -- Juvenile films; Undercover operations -- Juvenile films; Birthdays -- Juvenile films; Animated television programs; Television programs for children; Television programs for the hearing impaired